(untitled) (Bangladesh Journal of Pharmacology, 2017)
In this study, the anti-inflammatory potential of Anredera cordifolia and Piper crocatum extracts on lipopolysaccharide-induced murine macrophage cell line (RAW 264.7) was observed. Cell viability assay was performed with MTS assay. Parameters measured to determine the anti-inflammatory activity were interleukin-1? (IL-1?), tumor necrosis factor (TNF)-?, nitric oxide (NO) and IL-6. Both A. cordifolia and P. crocatum at concentration of 50 µg/mL in cell line resulted significant decrease in TNF-? level (250.3 and 242.5 pg/mL respectively). A. cordifolia showed significant decrease in IL-1? level at 50 µg/mL and IL-6 level at 10 µg/mL, whilst P. crocatum showed significant decrease IL-1? level in three concentrations with lowest level at 50 µg/mL. A. cordifolia showed lowest decrease in NO level at 50 µg/mL but not comparable with normal cells, whilst P. crocatum showed significant decrease in NO level at 50 µg/mL. This research revealed that A. cardi folia and P. crocatum possess the anti-inflammatory potential indicated by the inhibitory activity of the inflammatory mediators including, TNF-?, IL-1?, IL-6, and NO. Video Clip of Methodology: Viability Assay: 4 min 8 sec Full Screen Alternate